IS ACQUISITION OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS - AN OCCUPATIONAL HAZARD FOR MEDICAL STUDENTS IN INDIA? - K, Shreyas; M, Radhakrishna; Hegde, Ashwini; Rao, Pooja (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The incidence of community-acquired and hospital-acquired Staphylococcus aureus infections has been rising with increasing emergence of drug-resistant strains called methicillin-resistant S. aureus (MRSA). The main objective of this study was to determine the prevalence of carriage rate of MRSA among the interns of tertiary care teaching hospital in Mangalore. Methods: A total of 150 interns were participated, thereby swabs from both anterior nares were collected and processed for S. aureus. The isolated strains of S. aureus were screened for methicillin susceptibility by modified Kirbyâ€“Bauer method using cefoxitin (30 Î¼g) disc. Further, antibiotic susceptibility testing for all isolates of S. aureus was also done against selected appropriate antibiotics. Vancomycin susceptibility testing for MRSA was done by E test. Results: The number of strains of S. aureus isolated from our 150 participants was 71 with a percentage rate of 47.3. Of the 71 isolates of S. aureus, one (1.4%) was MRSA. The overall MRSA carriage rate was 0.66%. The S. aureus and MRSA carriage rates recorded in this study were at par and significantly lower, respectively, when compared with other reported studies. It was observed that risk factors such as the use of antibiotics in the past 6 months and smoking were found to be statistically significant in nasal carriage status of S. aureus (<0.05). The only one isolate of MRSA was found to be sensitive to vancomycin, linezolid, and teicoplanin. Conclusion: It was concluded that the acquisition of S. aureus and MRSA would not be an occupational hazard for medical students of developing countries like India.